Assessing alternative industrial fortification portfolios: A Bangladesh case study - Fiedler, John L.; Lividini, Keith; Guyondet, Christophe; Bermudez, Odilia I. (SAGE Publications, 2015)
Approximately 1.2 million disability-adjusted life years (DALYs) are lost annually in Bangladesh due to deficiencies of vitamin A, iron, and zinc.To provide evidence on the coverage, costs, and cost-effectiveness of alternative fortification interventions to inform nutrition policy-making in Bangladesh.Combining the 2005 Bangladesh Household Income and Expenditure Survey with a Bangladesh food composition table, apparent intakes of energy, vitamin A, iron, and zinc, and the coverage and apparent consumption levels of fortifiable vegetable oil and wheat flour are estimated. Assuming that fortification levels are those established in official regulations, the costs and cost-effectiveness of the two vehicles are assessed independently and as a two-vehicle portfolio.Vegetable oil has a coverage rate of 76% and is estimated to reduce the prevalence of inadequate vitamin A intake from 83% to 64%. The coverage of wheat flour is high (65%), but the small quantities consumed result in small reductions in the prevalence of inadequate intakes: 1.5 percentage points for iron, less than 1 for zinc, and 2 for vitamin A, while reducing average Estimated Average Requirement (EAR) gaps by 8%, 9%, and 15%, respectively. The most cost-effective 10-micronutrient wheat flour formulation costs US$1.91 million annually, saving 129,212 DALYs at a unit cost of US$14.75. Fortifying vegetable oil would cost US$1.27 million annually, saving 406,877 DALYs at an average cost of US$3.25. Sensitivity analyses explore various permutations of the wheat flour formulation. Divisional variations in coverage, cost, and impact are examined.Vegetable oil fortification is the most cost-effective of the three portfolios analyzed, but all three are very cost-effective options for Bangladesh.